Tapping Into Self-Efficacy And Learning Facilities For Enhanced Academic Achievement: A Case Study Of Mi Nu Brebek Waru Students - M. Jamal Abdul Naser; Didit Darmawan (Hikamatzu | Journal of Multidisciplinary, 2024)
This study seeks to quantitatively examine how self-efficacy and learning facilities influence student learning outcomes at MI NU Brebek Waru. The study encompasses all 323 students enrolled at MI NU Brebek Waru, constituting the study population. Through rigorous analysis, the research aims to elucidate the extent to which self-efficacy and the availability of learning facilities impact students' academic achievements within this educational context. To maintain the representativeness of the population, this study selected a sample from a group of Class VI students totalling 45 students. Data analysis was conducted using regression techniques to determine the extent to which self-efficacy and learning facilities can predict student learning outcomes. The findings from this study can provide a positive and significant contribution to self-efficacy and learning facilities to student learning outcomes. By understanding the extent to which self-efficacy and learning facilities influence learning outcomes, it is hoped that this study can provide valuable recommendations for schools, teachers and parents in improving learning conditions and students' academic performance